2001
DOI: 10.1073/pnas.101137598
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis nph1 and npl1: Blue light receptors that mediate both phototropism and chloroplast relocation

Abstract: UV-A͞blue light acts to regulate a number of physiological processes in higher plants. These include light-driven chloroplast movement and phototropism. The NPH1 gene of Arabidopsis encodes an autophosphorylating protein kinase that functions as a photoreceptor for phototropism in response to low-intensity blue light. However, nph1 mutants have been reported to exhibit normal phototropic curvature under high-intensity blue light, indicating the presence of an additional phototropic receptor. A likely candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
725
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 676 publications
(763 citation statements)
references
References 30 publications
26
725
3
3
Order By: Relevance
“…To test whether light perception by these photoreceptors is required for P. syringae-induced defense responses and disease resistance, we examined the interactions of the following Arabidopsis double mutants impaired in either cryptochrome, phototropin, or phytochrome photoperception, with an avirulent (Psm avrRpm1) or a virulent strain (Psm) of P. syringae pv. maculicola: cry1cry2 (cry1-304 cry2-1; Mockler et al, 1999), phot1phot2 (phot1-5 phot2-1; Sakai et al, 2001), and phyAphyB (phyA-211 phyB-9; Cerdán and Chory, 2003). Common genetic background for all examined mutants is accession Col (Col-0 for cry1cry2 and phyAphyB; Col-3 for phot1phot2), implicating that each line harbors the resistance gene Rpm1 whose product recognizes the bacterial avirulence protein AvrRpm1.…”
Section: Photoreceptor Signaling Only Moderately Affects Induction Ofmentioning
confidence: 99%
“…To test whether light perception by these photoreceptors is required for P. syringae-induced defense responses and disease resistance, we examined the interactions of the following Arabidopsis double mutants impaired in either cryptochrome, phototropin, or phytochrome photoperception, with an avirulent (Psm avrRpm1) or a virulent strain (Psm) of P. syringae pv. maculicola: cry1cry2 (cry1-304 cry2-1; Mockler et al, 1999), phot1phot2 (phot1-5 phot2-1; Sakai et al, 2001), and phyAphyB (phyA-211 phyB-9; Cerdán and Chory, 2003). Common genetic background for all examined mutants is accession Col (Col-0 for cry1cry2 and phyAphyB; Col-3 for phot1phot2), implicating that each line harbors the resistance gene Rpm1 whose product recognizes the bacterial avirulence protein AvrRpm1.…”
Section: Photoreceptor Signaling Only Moderately Affects Induction Ofmentioning
confidence: 99%
“…Mutants of Arabidopsis impaired in hypocotyl phototropism were isolated (Khurana and Poff, 1989;Liscum and Briggs, 1996), and molecular genetic analysis of these mutants has lead to the discovery of novel proteins that participate in the early process of phototropism. Most importantly, phototropin 1 (phot1) was uncovered as the major photoreceptor for phototropism (Huala et al, 1997) and phototropin 2 (phot2) as an additional photoreceptor that functions at high fluence rates (Sakai et al, 2001) (for the receptor nomenclature, see Briggs et al, 2001). The protein NPH3 was identified as a signaling component that is essential for hypocotyl phototropism and probably functions by directly interacting with phot1 (Motchoulski and Liscum, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Its potential role as the second phototropic receptor was cemented when Sakai and colleagues (2001) determined that phot1phot2 double mutants lack phototropic response in both low and high fluence rate blue light. However, phot2 single mutants retained an essentially wildtype response under all fluence rates tested (Sakai et al, 2001). It was therefore concluded that phot1 and phot2 function redundantly as high light receptors, while phot1 acts as the low-light photoreceptor (Sakai et al, 2001).…”
Section: Saw the Lightmentioning
confidence: 99%
“…However, phot2 single mutants retained an essentially wildtype response under all fluence rates tested (Sakai et al, 2001). It was therefore concluded that phot1 and phot2 function redundantly as high light receptors, while phot1 acts as the low-light photoreceptor (Sakai et al, 2001). The phototropins are members of a larger family of sensor proteins known as the LOV domain family (Crosson et al, 2003).…”
Section: Saw the Lightmentioning
confidence: 99%